Dinâmica da participação em órgãos colegiados : estudo de casos do IFSULDEMINAS-Campus Machado - Moraes, Elivan Afonso (2015)
This research whose the development was made through a case study it aims to analysis and subsequent evaluation of the effectiveness of collegiate bodies of IFSULDEMINAS-Campus Machado from the point of view of participation and participatory processes. Among the effectiveness existing concepts, it was adopted in this work which deals with the ability of institutions must produce results. This study model has been widely used in participatory institutions at the federal, state and municipal levels, in different public policy sectors, such as environment, health, social assistence, among others. He proposed the same discussion but adapted to collegiate bodies of an educational institution and it was possible to verify whether these channels actually meet the objectives for which they were created. These organisms are made in areas where debate various topics affecting the daily life of the academic community, so these are highly relevant participatory mechanisms. The followed study described by Vaz (2011), identifying the specific factors that influence and / or cause some extent the variation in results and consequently affect the ability of the organs to influence the actions and decision making. In this sense, three variables were used in the search: deliberative effectiveness, institutional design and exogenous factors. The results point to the existence of failures in all organs, to a greater or lesser extent. At the end some recommendations are shown to Campus Machado managers for correction purposes of the deficiencies.